A MARINE INVASION STORY: CAULERPA CYLINDRACEA (CHLOROPHYTA, ULVOPHYCEAE) IN THE MARINE PROTECTED AREA OF PORTOFINO (LIGURIAN SEA) - Mancini, Ilaria; Bianchi, Carlo Nike; Morri, Carla; Azzola, Annalisa; Oprandi, Alice; Robello, Chiara; Montefalcone, Monica (Biologia Marina Mediterranea, 2024)
The green alga Caulerpa cylindracea, one of the worst invasive species in the Mediterranean Sea, was first recorded in the Portofino Marine Protected Area (Ligurian Sea, NW Mediterranean) in 2008, where it was more abundant in the circalittoral (21 m to 45 m depth) than in the infralittoral zone (1 m to 20 m). Monitoring between 2012 and 2021 showed that, notwithstanding high yearly variability, it was widespread at all depths, with minor differences between the infralittoral and the circalittoral. However, recent monitoring data showed that the alga decreased its cover at all depths, to virtually disappear in 2023. This temporal pattern recalls that of the congeneric C. taxifolia, which – after an impressive initial bloom – did not persist in most of the Ligurian Sea.